THE IMPACT OF BRAND EQUITY AND BRAND TRUST TOWARDS PURCHASE INTENTION THROUGH BRAND PREFERENCE - Scherly Hansopaheluwakan , Elia Oey , Yohanes Setiawan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The high demand for bottled water makes the growth of bottled water industry growing rapidly. This is marked by the number of brands of bottled water that makes competition in the bottled water industry more intense. This study aims to determine the direct and indirect effect of brand equity and brand trust on buying interest through brand preference in bottled water consumers in Tangerang City. The sample used is 170 respondents from society of Tangerang City which is determined using purposive sampling method. Data collection was done by distributing online questionnaires to respondents. This research is a quantitative research using structural equation model (SEM) data analysis method. The results of this study indicate that brand equity has a positive and significant effect on buying interest, either directly or indirectly through brand preference. Directly, brand trust has a positive but insignificant effect on buying interest. Simultaneously, brand equity and brand trust have a positive and significant effect on buying interest through brand preference.